ANALYST COVERAGE, INFORMATION ASYMMETRY, AND ACCOUNTING CONSERVATISM: EVIDENCE FROM INDONESIAN MANUFACTURING FIRMS - Nurbatin, Defia (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2025)
The purpose of this study was to examine the effect of analyst coverage on information asymmetry and accounting conservatism in the manufacturing sector. Data processing and analysis testing in this study was carried out using Eviews 19. The researcher's initial analysis showed that there were 19 manufacturing companies listed on the Indonesia Stock Exchange (IDX) which became the research sample. On this basis, this study analyzed 190 companies during the observation period, namely 2010 - 2019. Then the test results can be concluded that 1) analyst coverage does not significantly affect information asymmetry; 2) analyst coverage does not significantly affect accounting conservatism. This research is expected to provide input for regulators in evaluating the effectiveness of the role of analyst coverage as an external monitoring mechanism. In addition, the results of this study are expected to provide an evaluation of the role of analyst coverage related to the quality of the analysis produced especially for investors in making investment decisions.